Co-creation rules - Cherkoff, James; Moore, Johnnie (Henry Stewart Talks, 2008)
Market research used to happen before the product was developed, and it was done to customers, Now major brands are creating the products and promotion in real time, and with their customers, Examples of co-creation, How to make it work for you